Efektifitas Antibiotik pada Pasien Ulkus Kaki Diabetik - Nesa Agistia; Husni Mukhtar; Hansen Nasif (Fakultas Farmasi Universitas Andalas, 2017)
Patients with diabetic foot infection require antibiotics. Generally, antibiotics may have low sensitivity and some bacteria have been resistance to antibiotics. Currently, evaluating the effectiveness of antibiotics is necessary to avoid antibiotic resistance. This study has been conducted using the longitudinal method and prospective sampling technique. Observed parameters were leukocyte, signs of infection and fever after using antibiotics. The data collected were then analyzed to determine the effectiveness of antibiotics based on supporting literature. A number of 19 out of 28 samples of patients with diabetic foot ulcer met the criteria, consisting of 63.16% and 36.84% of male and female patients, respectively. Most of the patients (68,42%) were aged 45-60 years old living with diabetes for more than 10 years. The antimicrobial therapy were given empirically in 8 patients (42,10%) and based on microbial sensitivity (definitive) in 11 patients (57,89%). The use of antibiotics was effective in 15 patients (78,94%) marked by the leukocyte count, signs of infection and fever parameters after 2-3 days using antibiotics. The optimum therapeutic outcome was achieved in 7 to 21 days.